Super-wear-resistant and efficient antifouling ceramic tile and preparation method thereof
Through the combination of specific processes and raw materials, ultra-wear-resistant and efficient anti-fouling tiles are prepared, which solves the problems of insufficient wear resistance, susceptibility to pollution and lack of anti-bacterial properties of traditional ceramic tiles, and achieves higher wear resistance, anti-fouling and anti-bacterial properties, extends service life and enhances market competitiveness.
Patent Information
- Application Number
- CN202411847078.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional ceramic tiles have problems such as insufficient wear resistance, susceptibility to pollution and lack of antibacterial properties during use, which limits their application scope, especially in places with high requirements for hygiene and aesthetics.
Ultra-wear-resistant and efficient anti-fouling tiles are prepared through specific mixing, crushing, slurry preparation, press molding, drying, sintering, polishing and applying wear-resistant and anti-fouling coatings.
It improves the wear resistance and stain resistance of ceramic tiles, enhances antibacterial properties, ensures the cleanliness and hygiene of ceramic tiles, extends the service life, is suitable for public areas with large flow of people, and enhances the market competitiveness of ceramic tiles.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramic tiles, and in particular relates to a ceramic tile with super wear resistance and high efficiency antifouling properties and a preparation method thereof. Background Art
[0002] Ceramic tile, also known as ceramic tile, is a common building and decoration material. It is made of inorganic non-metallic raw materials such as clay, quartz, and feldspar through mixing, molding, drying, and high-temperature sintering. Ceramic tiles are hard, wear-resistant, acid- and alkali-resistant, corrosion-resistant, easy to clean, and highly decorative. They are widely used in the decoration of indoor and outdoor walls, floors, kitchen countertops, bathtubs, and other areas. The basic structure of ceramic tiles usually includes the following parts: Body: The body is the main part of the tile. It is made of ceramic raw materials that are mixed and molded and then sintered. It determines the strength and stability of the tile. Glaze: The glaze is a glassy layer covering the surface of the body. It can improve the gloss, wear resistance, and stain resistance of the tile, while providing rich colors and patterns. Pattern layer: The pattern layer is located under the glaze. The pattern and color are applied to the body through screen printing, inkjet printing, and other technologies, and then covered with a glaze layer, so that the tile has various decorative effects.
[0003] However, traditional ceramic tiles have some problems during use, such as insufficient wear resistance, susceptibility to pollution, lack of antibacterial properties, etc. These problems limit the application scope of ceramic tiles, especially in places with high requirements for hygiene and aesthetics. Summary of the invention
[0004] The object of the present invention is to provide a super wear-resistant and highly effective anti-fouling ceramic tile and a preparation method thereof in order to solve the above-mentioned problems.
[0005] The technical solution adopted by the present invention is as follows: a super wear-resistant and highly effective anti-fouling ceramic tile, the ceramic tile comprising:
[0006] Kaolin: 40-50 parts by mass;
[0007] Quartz: 20-30 parts by mass;
[0008] Feldspar: 15-25 parts by mass;
[0009] Natural stone powder: 20-40 parts by mass;
[0010] Water: 20-30 parts by weight;
[0011] Nano ceramics or silicates: 1-5 parts by mass;
[0012] 4-6 parts by weight of antibacterial agent;
[0013] 2-3 parts by mass of flux;
[0014] Dispersant 4-6 parts by mass;
[0015] Colorant 5-8 parts by weight
[0016] In a preferred embodiment, the preparation method comprises the following steps:
[0017] S1: First, weigh the raw materials for preparing super wear-resistant and highly effective antifouling tiles:
[0018] Kaolin: 40-50 parts by mass;
[0019] Quartz: 20-30 parts by mass;
[0020] Feldspar: 15-25 parts by mass;
[0021] Natural stone powder: 20-40 parts by mass;
[0022] Water: 20-30 parts by weight;
[0023] Nano ceramics or silicates: 1-5 parts by mass;
[0024] 4-6 parts by weight of antibacterial agent;
[0025] 2-3 parts by mass of flux;
[0026] Dispersant 4-6 parts by mass;
[0027] Colorant 5-8 parts by mass;
[0028] S2: Mix the raw materials weighed in step S1 according to the weighed proportions and stir evenly;
[0029] S3: Grinding and refining the mixed raw materials to ensure uniform particle size;
[0030] S4: preparing slurry, adding appropriate amount of water to the crushed raw materials to prepare ceramic slurry;
[0031] S5: pressing and molding, pressing the ceramic slurry through a press to form a ceramic tile body;
[0032] S6: Drying: drying the pressed tile body to remove excess water;
[0033] S7: placing the dried ceramic tile body into a high temperature furnace for sintering, and the sintering temperature is controlled at 1200-1300°C;
[0034] S8: After sintering is completed, let the tiles cool naturally to room temperature;
[0035] S9: Polish the fired tiles to improve the glossiness of the tiles surface;
[0036] S10: Apply a layer of wear-resistant and anti-fouling coating on the surface of the tile. The coating material can be nano-ceramics, silicate, etc.
[0037] S11: Curing the tiles with the wear-resistant and anti-fouling coating to ensure that the coating is tightly bonded to the tiles, thereby improving the wear resistance and anti-fouling properties. The prepared tiles are collected and stored, thereby completing the entire preparation process of the super wear-resistant and highly effective anti-fouling tiles.
[0038] In a preferred embodiment, in step S1, the natural stone powder is one of granite powder and marble powder;
[0039] In step S1, the flux is one or more of sodium oxide, potassium oxide, calcium oxide or magnesium oxide;
[0040] The dispersant is one or more of sodium polyacrylate, hydroxypropyl methylcellulose or polyvinyl alcohol.
[0041] The colorant is one or more of iron oxide, chromium oxide, cobalt oxide, copper oxide or tin oxide.
[0042] In a preferred embodiment, in the step S1, the preparation method of the antibacterial agent is as follows: first, chitosan oligosaccharide particles, n-octane and antibacterial nano zinc ions are added to a reaction vessel, and high-frequency ultrasound is used to disperse and stir to form a chitosan oligosaccharide-n-octane dispersion system. Then, isophthaloyl chloride is added, and triethylamine is introduced as a Lewis base, and water bath heating is performed for 1 hour while ultrasonic stirring. After natural cooling, the modified chitosan oligosaccharide powder is obtained by spray drying technology. Subsequently, the modified chitosan oligosaccharide powder is dissolved in deionized water, the pH value is adjusted to 6, and 0.6 mol / L zinc sulfate solution is added under magnetic stirring conditions, and ultrasonic stirring is reacted for 40 minutes. Subsequently, sodium hydroxide is slowly added dropwise to raise the pH value to 9 within 30 minutes, and the solid matter is collected by filtration and washed three times with deionized water. Finally, mint leaf powder and forsythia fiber powder are added to the product, and vacuum freeze-dried to obtain a plant-derived chitosan oligosaccharide-zinc oxide composite antibacterial agent.
[0043] In a preferred embodiment, in step S1, during the mixing process, it is necessary to ensure that all raw materials are evenly distributed to avoid agglomeration and segregation. The mixing time is controlled to be 30-60 minutes, and the specific time depends on the type and efficiency of the mixer. After the mixing is completed, the mixture should be sampled and tested to ensure that the mixing ratio is accurate;
[0044] In step S2, the grinding and refining is carried out in a ball mill or a vibration mill to ensure that the particle size distribution of the raw material is uniform and the average particle size is controlled within the range of 1-10 microns. The grinding and refining time is 2-4 hours, and the specific time depends on the initial particle size of the raw material and the required particle size distribution.
[0045] In a preferred embodiment, in step S3, the purpose of pulverizing is to ensure that the particle size distribution of the raw material is uniform, and the average particle size is controlled within the range of 1-10 microns. The pulverizing time is 2-4 hours, and the specific time depends on the initial particle size of the raw material and the required particle size distribution;
[0046] In step S4, the crushed raw material is added with 20% to 30% of water of the total raw material mass, and stirred evenly in a mixer to prepare a ceramic slurry. The consistency of the slurry is controlled within a suitable range to facilitate subsequent pressing and molding. The pH value of the slurry needs to be adjusted to 7-8 to ensure optimal stability and fluidity.
[0047] In a preferred embodiment, in step S5, during the pressing process, the pressure is controlled at 30-50 MPa to obtain a dense and uniform tile body. The pressing time is 15-30 seconds, and the specific time depends on the performance of the press and the characteristics of the slurry. The thickness and size of the green body after pressing must meet the predetermined specifications.
[0048] In a preferred embodiment, in step S6, the drying process can be carried out in a drying chamber or a tunnel dryer, the temperature is controlled at 60-100° C., and the drying time is 12-24 hours, and the specific time depends on the thickness of the green body and the performance of the drying equipment;
[0049] In step S7, the sintering temperature is controlled at 1200-1300°C, the heating rate is about 2-5°C / minute, and the holding time is 1-2 hours to ensure that the internal structure of the tile is uniform and dense. During the sintering process, the atmosphere in the furnace needs to be strictly controlled to avoid the influence of oxidizing or reducing atmosphere on the performance of the tile.
[0050] In a preferred embodiment, in step S8, after sintering is completed, the tile is allowed to cool naturally to room temperature. The natural cooling rate should not be too fast to prevent the tile from cracking due to a large temperature gradient. The cooling time is 12-24 hours, and the specific time depends on the size and thickness of the tile;
[0051] In step S9, during the polishing process, a polishing machine is used with polishing abrasive blocks, and the abrasive blocks are used in order from coarse to fine particles to gradually improve the glossiness of the tile surface. The polishing pressure and speed need to be adjusted according to the hardness of the tile and the required polishing effect.
[0052] In a preferred embodiment, in step S10, the coating material may be nano-ceramic or silicate, and the coating may be applied by spraying, brushing or dipping. The coating thickness is controlled to be 5-20 microns to ensure sufficient wear resistance and antifouling performance. After applying the coating, it is necessary to ensure that the coating evenly covers the surface of the tile.
[0053] In the step S11, the curing process is carried out in an oven, the temperature is controlled at 100-150° C., and the curing time is about 30-60 minutes.
[0054] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0055] 1. In the present invention, during the preparation process, a highly efficient composite antibacterial agent is formed by combining chitosan oligosaccharides with nano zinc ions. This composite antibacterial agent can inhibit the growth and reproduction of microorganisms such as bacteria and molds on the surface of ceramic tiles, thereby keeping the ceramic tiles clean and hygienic. Especially in humid environments such as kitchens and bathrooms, this antibacterial property is particularly important, as it can reduce bacterial growth and protect the health of users. In addition, through ultrasonic stirring and spray drying technology, the antibacterial agent can be evenly distributed on the surface of the ceramic tile, ensuring that every part of the ceramic tile has an antibacterial effect. Finally, the introduction of the plant-derived chitosan oligosaccharide-zinc oxide composite antibacterial agent not only enhances the antibacterial properties of the ceramic tile, but also increases its environmental protection and sustainability, which is of great significance for improving the market competitiveness of ceramic tiles.
[0056] 2. In the present invention, the addition of natural stone significantly improves the wear resistance of ceramic tiles. Since natural stone itself has the characteristics of high hardness and good wear resistance, adding its powder to the raw materials of ceramic tiles can effectively improve the hardness and wear resistance of the ceramic tile surface. The ceramic tiles prepared in this way can better resist wear and tear during use and extend their service life, and are particularly suitable for public areas with large traffic. The natural texture and color of natural stone add a natural and beautiful appearance to the ceramic tiles, and enhance the decorative effect and grade of the ceramic tiles. In addition, the addition of natural stone can also enhance the anti-fouling performance of ceramic tiles, because the stone itself has a certain anti-fouling ability, which can reduce the penetration of stains, making the ceramic tiles easier to clean and maintain. These characteristics make ceramic tiles with added natural stone ingredients more attractive in the market and meet consumers' pursuit of high-quality life. DETAILED DESCRIPTION
[0057] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0058] Embodiment 1:
[0059] A super wear-resistant and highly stain-resistant tile, comprising:
[0060] Kaolin: 40 parts by mass;
[0061] Quartz: 20 parts by mass;
[0062] Feldspar: 15 parts by mass;
[0063] Natural stone powder: 20 parts by mass;
[0064] Water: 20 parts by mass;
[0065] Nano ceramics or silicate: 1 part by mass;
[0066] 4 parts by weight of antibacterial agent;
[0067] 2 parts by mass of flux;
[0068] 4 parts by mass of dispersant;
[0069] Colorant 5 parts by mass
[0070] The preparation method comprises the following steps:
[0071] S1: First, weigh the raw materials for preparing super wear-resistant and highly effective antifouling tiles:
[0072] Kaolin: 40 parts by mass;
[0073] Quartz: 20 parts by mass;
[0074] Feldspar: 15 parts by mass;
[0075] Natural stone powder: 20 parts by mass;
[0076] Water: 20 parts by mass;
[0077] Nano ceramics or silicate: 1 part by mass;
[0078] 4 parts by weight of antibacterial agent;
[0079] 2 parts by mass of flux;
[0080] 4 parts by mass of dispersant;
[0081] Colorant 5 parts by mass;
[0082] S2: Mix the raw materials weighed in step S1 according to the weighed proportions and stir evenly;
[0083] S3: Grinding and refining the mixed raw materials to ensure uniform particle size;
[0084] S4: preparing slurry, adding appropriate amount of water to the crushed raw materials to prepare ceramic slurry;
[0085] S5: pressing and molding, pressing the ceramic slurry through a press to form a ceramic tile body;
[0086] S6: Drying: drying the pressed tile body to remove excess water;
[0087] S7: placing the dried ceramic tile body into a high temperature furnace for sintering, and the sintering temperature is controlled at 1200-1300°C;
[0088] S8: After sintering is completed, let the tiles cool naturally to room temperature;
[0089] S9: Polish the fired tiles to improve the glossiness of the tiles surface;
[0090] S10: Apply a layer of wear-resistant and anti-fouling coating on the surface of the tile. The coating material can be nano-ceramics, silicate, etc.
[0091] S11: Curing the tiles with the wear-resistant and anti-fouling coating to ensure that the coating is tightly bonded to the tiles, thereby improving the wear resistance and anti-fouling properties. The prepared tiles are collected and stored, thereby completing the entire preparation process of the super wear-resistant and highly effective anti-fouling tiles.
[0092] In the step S1, the natural stone powder is one of granite powder and marble powder;
[0093] In step S1, the flux is one or more of sodium oxide, potassium oxide, calcium oxide or magnesium oxide;
[0094] The dispersant is one or more of sodium polyacrylate, hydroxypropyl methylcellulose or polyvinyl alcohol.
[0095] The colorant is one or more of iron oxide, chromium oxide, cobalt oxide, copper oxide or tin oxide.
[0096] In the step S1, the preparation method of the antibacterial agent is as follows: first, chitosan oligosaccharide particles, n-octane and antibacterial nano zinc ions are added to a reaction vessel, and high-frequency ultrasound is used for dispersion and stirring to form a chitosan oligosaccharide-n-octane dispersion system. Then, isophthaloyl chloride is added, and triethylamine is introduced as a Lewis base, and water bath heating is performed for 1 hour while ultrasonic stirring. After natural cooling, the modified chitosan oligosaccharide powder is obtained by spray drying technology. Subsequently, the modified chitosan oligosaccharide powder is dissolved in deionized water, the pH value is adjusted to 6, and 0.6 mol / L zinc sulfate solution is added under magnetic stirring conditions, and ultrasonic stirring is reacted for 40 minutes. Subsequently, sodium hydroxide is slowly added dropwise to raise the pH value to 9 within 30 minutes, and the solid matter is collected by filtration and washed three times with deionized water. Finally, mint leaf powder and forsythia fiber powder are added to the product, and vacuum freeze-dried to obtain a plant-derived chitosan oligosaccharide-zinc oxide composite antibacterial agent.
[0097] In step S1, during the mixing process, it is necessary to ensure that all raw materials are evenly distributed to avoid agglomeration and segregation. The mixing time is controlled to be 30-60 minutes, and the specific time depends on the type and efficiency of the mixer. After the mixing is completed, the mixture should be sampled and tested to ensure that the mixing ratio is accurate;
[0098] In step S2, the grinding and refining is carried out in a ball mill or a vibration mill to ensure that the particle size distribution of the raw material is uniform and the average particle size is controlled within the range of 1-10 microns. The grinding and refining time is 2-4 hours, and the specific time depends on the initial particle size of the raw material and the required particle size distribution.
[0099] In step S3, the purpose of pulverization is to ensure that the particle size distribution of the raw material is uniform and the average particle size is controlled within the range of 1-10 microns. The pulverization time is 2-4 hours, and the specific time depends on the initial particle size of the raw material and the required particle size distribution;
[0100] In step S4, the crushed raw material is added with 20% to 30% of water of the total raw material mass, and stirred evenly in a mixer to prepare a ceramic slurry. The consistency of the slurry is controlled within an appropriate range to facilitate subsequent pressing and molding. The pH value of the slurry needs to be adjusted to 7-8 to ensure optimal stability and fluidity.
[0101] In step S5, during the pressing process, the pressure is controlled at 30-50 MPa to obtain a dense and uniform tile body. The pressing time is 15-30 seconds, and the specific time depends on the performance of the press and the characteristics of the slurry. The thickness and size of the green body after pressing must meet the predetermined specifications.
[0102] In step S6, the drying process can be carried out in a drying chamber or a tunnel dryer, the temperature is controlled at 60-100°C, and the drying time is 12-24 hours, and the specific time depends on the thickness of the green body and the performance of the drying equipment;
[0103] In step S7, the sintering temperature is controlled at 1200-1300°C, the heating rate is about 2-5°C / minute, and the holding time is 1-2 hours to ensure that the internal structure of the tile is uniform and dense. During the sintering process, the atmosphere in the furnace needs to be strictly controlled to avoid the influence of oxidizing or reducing atmosphere on the performance of the tile.
[0104] In step S8, after sintering is completed, the tile is allowed to cool naturally to room temperature. The natural cooling rate should not be too fast to prevent the tile from cracking due to a large temperature gradient. The cooling time takes 12-24 hours, depending on the size and thickness of the tile;
[0105] In step S9, during the polishing process, a polishing machine is used with polishing abrasive blocks, and the abrasive blocks are used in order from coarse to fine particles to gradually improve the glossiness of the tile surface. The polishing pressure and speed need to be adjusted according to the hardness of the tile and the required polishing effect.
[0106] In step S10, the coating material may be nano-ceramic or silicate, and the coating may be applied by spraying, brushing or dipping. The coating thickness is controlled to be 5-20 microns to ensure sufficient wear resistance and antifouling performance. After applying the coating, it is necessary to ensure that the coating evenly covers the surface of the tile.
[0107] In the step S11, the curing process is carried out in an oven, the temperature is controlled at 100-150° C., and the curing time is about 30-60 minutes.
[0108] In the present invention, during the preparation process, a highly efficient composite antibacterial agent is formed by combining chitosan oligosaccharides with nano zinc ions. This composite antibacterial agent can inhibit the growth and reproduction of microorganisms such as bacteria and molds on the surface of ceramic tiles, thereby keeping the ceramic tiles clean and hygienic. Especially in humid environments such as kitchens and bathrooms, this antibacterial property is particularly important, as it can reduce bacterial growth and protect the health of users. In addition, through ultrasonic stirring and spray drying technology, the antibacterial agent can be evenly distributed on the surface of the ceramic tile, ensuring that every part of the ceramic tile has an antibacterial effect. Finally, the introduction of the plant-derived chitosan oligosaccharide-zinc oxide composite antibacterial agent not only enhances the antibacterial properties of the ceramic tile, but also increases its environmental protection and sustainability, which is of great significance for improving the market competitiveness of the ceramic tile.
[0109] In the present invention, the addition of natural stone significantly improves the wear resistance of the ceramic tile. Since the natural stone itself has the characteristics of high hardness and good wear resistance, adding its powder to the ceramic tile raw material can effectively improve the hardness and wear resistance of the ceramic tile surface. The ceramic tile prepared in this way can better resist wear and tear during use, extend its service life, and is particularly suitable for public areas with a large flow of people. The natural texture and color of the natural stone add a natural and beautiful appearance to the ceramic tile, and enhance the decorative effect and grade of the ceramic tile. In addition, the addition of natural stone can also enhance the anti-fouling performance of the ceramic tile, because the stone itself has a certain anti-fouling ability, which can reduce the penetration of stains, making the ceramic tile easier to clean and maintain. These characteristics make the ceramic tile with added natural stone components more attractive in the market, satisfying consumers' pursuit of high-quality life.
[0110] Embodiment 2:
[0111] A super wear-resistant and highly stain-resistant tile, comprising:
[0112] Kaolin: 50 parts by mass;
[0113] Quartz: 30 parts by mass;
[0114] Feldspar: 25 parts by mass;
[0115] Natural stone powder: 40 parts by mass;
[0116] Water: 30 parts by mass;
[0117] Nano ceramics or silicate: 5 parts by mass;
[0118] 6 parts by weight of antibacterial agent;
[0119] 3 parts by mass of flux;
[0120] Dispersant 6 parts by mass;
[0121] Colorant 8 parts by mass
[0122] The preparation method comprises the following steps:
[0123] S1: First, weigh the raw materials for preparing super wear-resistant and highly effective antifouling tiles:
[0124] Kaolin: 50 parts by mass;
[0125] Quartz: 30 parts by mass;
[0126] Feldspar: 25 parts by mass;
[0127] Natural stone powder: 40 parts by mass;
[0128] Water: 30 parts by mass;
[0129] Nano ceramics or silicate: 5 parts by mass;
[0130] 6 parts by weight of antibacterial agent;
[0131] 3 parts by mass of flux;
[0132] Dispersant 6 parts by mass;
[0133] Colorant 8 parts by mass;
[0134] S2: Mix the raw materials weighed in step S1 according to the weighed proportions and stir evenly;
[0135] S3: Grinding and refining the mixed raw materials to ensure uniform particle size;
[0136] S4: preparing slurry, adding appropriate amount of water to the crushed raw materials to prepare ceramic slurry;
[0137] S5: pressing and molding, pressing the ceramic slurry through a press to form a ceramic tile body;
[0138] S6: Drying: drying the pressed tile body to remove excess water;
[0139] S7: placing the dried ceramic tile body into a high temperature furnace for sintering, and the sintering temperature is controlled at 1200-1300°C;
[0140] S8: After sintering is completed, let the tiles cool naturally to room temperature;
[0141] S9: Polish the fired tiles to improve the glossiness of the tiles surface;
[0142] S10: Apply a layer of wear-resistant and anti-fouling coating on the surface of the tile. The coating material can be nano-ceramics, silicate, etc.
[0143] S11: Curing the tiles with the wear-resistant and anti-fouling coating to ensure that the coating is tightly bonded to the tiles, thereby improving the wear resistance and anti-fouling properties. The prepared tiles are collected and stored, thereby completing the entire preparation process of the super wear-resistant and highly effective anti-fouling tiles.
[0144] In the step S1, the natural stone powder is one of granite powder and marble powder;
[0145] In step S1, the flux is one or more of sodium oxide, potassium oxide, calcium oxide or magnesium oxide;
[0146] The dispersant is one or more of sodium polyacrylate, hydroxypropyl methylcellulose or polyvinyl alcohol.
[0147] The colorant is one or more of iron oxide, chromium oxide, cobalt oxide, copper oxide or tin oxide.
[0148] In the step S1, the preparation method of the antibacterial agent is as follows: first, chitosan oligosaccharide particles, n-octane and antibacterial nano zinc ions are added to a reaction vessel, and high-frequency ultrasound is used for dispersion and stirring to form a chitosan oligosaccharide-n-octane dispersion system. Then, isophthaloyl chloride is added, and triethylamine is introduced as a Lewis base, and water bath heating is performed for 1 hour while ultrasonic stirring. After natural cooling, the modified chitosan oligosaccharide powder is obtained by spray drying technology. Subsequently, the modified chitosan oligosaccharide powder is dissolved in deionized water, the pH value is adjusted to 6, and 0.6 mol / L zinc sulfate solution is added under magnetic stirring conditions, and ultrasonic stirring is reacted for 40 minutes. Subsequently, sodium hydroxide is slowly added dropwise to raise the pH value to 9 within 30 minutes, and the solid matter is collected by filtration and washed three times with deionized water. Finally, mint leaf powder and forsythia fiber powder are added to the product, and vacuum freeze-dried to obtain a plant-derived chitosan oligosaccharide-zinc oxide composite antibacterial agent.
[0149] In step S1, during the mixing process, it is necessary to ensure that all raw materials are evenly distributed to avoid agglomeration and segregation. The mixing time is controlled to be 30-60 minutes, and the specific time depends on the type and efficiency of the mixer. After the mixing is completed, the mixture should be sampled and tested to ensure that the mixing ratio is accurate;
[0150] In step S2, the grinding and refining is carried out in a ball mill or a vibration mill to ensure that the particle size distribution of the raw material is uniform and the average particle size is controlled within the range of 1-10 microns. The grinding and refining time is 2-4 hours, and the specific time depends on the initial particle size of the raw material and the required particle size distribution.
[0151] In step S3, the purpose of pulverization is to ensure that the particle size distribution of the raw material is uniform and the average particle size is controlled within the range of 1-10 microns. The pulverization time is 2-4 hours, and the specific time depends on the initial particle size of the raw material and the required particle size distribution;
[0152] In step S4, the crushed raw material is added with 20% to 30% of water of the total raw material mass, and stirred evenly in a mixer to prepare a ceramic slurry. The consistency of the slurry is controlled within an appropriate range to facilitate subsequent pressing and molding. The pH value of the slurry needs to be adjusted to 7-8 to ensure optimal stability and fluidity.
[0153] In step S5, during the pressing process, the pressure is controlled at 30-50 MPa to obtain a dense and uniform tile body. The pressing time is 15-30 seconds, and the specific time depends on the performance of the press and the characteristics of the slurry. The thickness and size of the green body after pressing must meet the predetermined specifications.
[0154] In step S6, the drying process can be carried out in a drying chamber or a tunnel dryer, the temperature is controlled at 60-100°C, and the drying time is 12-24 hours, and the specific time depends on the thickness of the green body and the performance of the drying equipment;
[0155] In step S7, the sintering temperature is controlled at 1200-1300℃, the heating rate is about 2-5℃ / minute, and the holding time is 1-2 hours to ensure that the internal structure of the tile is uniform and dense. During the sintering process, the atmosphere in the furnace must be strictly controlled to avoid the influence of oxidizing or reducing atmosphere on the performance of the tile.
[0156] In step S8, after sintering is completed, the tile is allowed to cool naturally to room temperature. The natural cooling rate should not be too fast to prevent the tile from cracking due to a large temperature gradient. The cooling time takes 12-24 hours, depending on the size and thickness of the tile;
[0157] In step S9, during the polishing process, a polishing machine is used in combination with polishing abrasive blocks, and the abrasive blocks are used in order from coarse to fine particles to gradually improve the glossiness of the tile surface. The polishing pressure and speed need to be adjusted according to the hardness of the tile and the required polishing effect.
[0158] In step S10, the coating material may be nano-ceramic or silicate, and the coating may be applied by spraying, brushing or dipping. The coating thickness is controlled to be 5-20 microns to ensure sufficient wear resistance and antifouling performance. After applying the coating, it is necessary to ensure that the coating evenly covers the surface of the tile.
[0159] In the step S11, the curing process is carried out in an oven, the temperature is controlled at 100-150° C., and the curing time is about 30-60 minutes.
[0160] In the present invention, during the preparation process, a highly efficient composite antibacterial agent is formed by combining chitosan oligosaccharides with nano zinc ions. This composite antibacterial agent can inhibit the growth and reproduction of microorganisms such as bacteria and molds on the surface of ceramic tiles, thereby keeping the ceramic tiles clean and hygienic. Especially in humid environments such as kitchens and bathrooms, this antibacterial property is particularly important, as it can reduce bacterial growth and protect the health of users. In addition, through ultrasonic stirring and spray drying technology, the antibacterial agent can be evenly distributed on the surface of the ceramic tile, ensuring that every part of the ceramic tile has an antibacterial effect. Finally, the introduction of the plant-derived chitosan oligosaccharide-zinc oxide composite antibacterial agent not only enhances the antibacterial properties of the ceramic tile, but also increases its environmental protection and sustainability, which is of great significance for improving the market competitiveness of the ceramic tile.
[0161] In the present invention, the addition of natural stone significantly improves the wear resistance of the ceramic tile. Since the natural stone itself has the characteristics of high hardness and good wear resistance, adding its powder to the ceramic tile raw material can effectively improve the hardness and wear resistance of the ceramic tile surface. The ceramic tile prepared in this way can better resist wear and tear during use, extend its service life, and is particularly suitable for public areas with a large flow of people. The natural texture and color of the natural stone add a natural and beautiful appearance to the ceramic tile, and enhance the decorative effect and grade of the ceramic tile. In addition, the addition of natural stone can also enhance the anti-fouling performance of the ceramic tile, because the stone itself has a certain anti-fouling ability, which can reduce the penetration of stains, making the ceramic tile easier to clean and maintain. These characteristics make the ceramic tile with added natural stone components more attractive in the market, satisfying consumers' pursuit of high-quality life.
[0162] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the term "comprise" or any other variant thereof is intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.
[0163] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A super wear-resistant and highly effective anti-fouling tile, characterized by: The tiles include: Kaolin: 40-50 parts by mass; Quartz: 20-30 parts by mass; Feldspar: 15-25 parts by mass; Natural stone powder: 20-40 parts by mass; Water: 20-30 parts by weight; Nano ceramics or silicates: 1-5 parts by mass; 4-6 parts by weight of antibacterial agent; 2-3 parts by mass of flux; Dispersant 4-6 parts by mass; Colorant 5-8 parts by mass 2. The super wear-resistant and highly effective antifouling ceramic tile and its preparation method as claimed in claim 1, characterized in that: The preparation method comprises the following steps: S1: First, weigh the raw materials for preparing super wear-resistant and highly effective antifouling tiles: Kaolin: 40-50 parts by mass; Quartz: 20-30 parts by mass; Feldspar: 15-25 parts by mass; Natural stone powder: 20-40 parts by mass; Water: 20-30 parts by weight; Nano ceramics or silicates: 1-5 parts by mass; 4-6 parts by weight of antibacterial agent; 2-3 parts by mass of flux; Dispersant 4-6 parts by mass; Colorant 5-8 parts by weight; S2: Mix the raw materials weighed in step S1 according to the weighed proportions and stir evenly; S3: Grinding and refining the mixed raw materials to ensure uniform particle size; S4: preparing slurry, adding appropriate amount of water to the crushed raw materials to prepare ceramic slurry; S5: pressing and molding, pressing the ceramic slurry through a press to form a ceramic tile body; S6: Drying: drying the pressed tile body to remove excess water; S7: placing the dried ceramic tile body into a high temperature furnace for sintering, and the sintering temperature is controlled at 1200-1300°C; S8: After sintering is completed, let the tiles cool naturally to room temperature; S9: Polish the fired tiles to improve the glossiness of the tiles surface; S10: Apply a layer of wear-resistant and anti-fouling coating on the surface of the tile. The coating material can be nano-ceramics or silicate; S11: Curing the tiles with the wear-resistant and anti-fouling coating to ensure that the coating is tightly bonded to the tiles, thereby improving the wear resistance and anti-fouling properties. The prepared tiles are collected and stored, thereby completing the entire preparation process of the super wear-resistant and highly effective anti-fouling tiles.
3. The super wear-resistant and highly effective antifouling ceramic tile and its preparation method as claimed in claim 1, characterized in that: In the step S1, the natural stone powder is one of granite powder and marble powder; In step S1, the flux is one or more of sodium oxide, potassium oxide, calcium oxide or magnesium oxide; The dispersant is one or more of sodium polyacrylate, hydroxypropyl methylcellulose or polyvinyl alcohol; The colorant is one or more of iron oxide, chromium oxide, cobalt oxide, copper oxide or tin oxide.
4. The super wear-resistant and highly effective antifouling ceramic tile and the preparation method thereof according to claim 1, characterized in that: In the step S1, the preparation method of the antibacterial agent is as follows: first, chitosan oligosaccharide particles, n-octane and antibacterial nano zinc ions are added to a reaction container, and high-frequency ultrasound is used for dispersion and stirring to form a chitosan oligosaccharide-n-octane dispersion system; then, isophthaloyl chloride is added, and triethylamine is introduced as a Lewis base, and water bath heating is performed for 1 hour while ultrasonic stirring; after natural cooling, modified chitosan oligosaccharide powder is obtained by spray drying technology; then, the modified chitosan oligosaccharide powder is dissolved in deionized water, the pH value is adjusted to 6, 0.6 mol / L zinc sulfate solution is added under magnetic stirring conditions, and ultrasonic stirring is used for reaction for 40 minutes; then, sodium hydroxide is slowly added dropwise to raise the pH value to 9 within 30 minutes, the solid matter is collected by filtration, and washed three times with deionized water; finally, mint leaf powder and forsythia fiber powder are added to the product, and vacuum freeze-drying is performed to obtain a plant-based chitosan oligosaccharide-zinc oxide composite antibacterial agent.
5. The super wear-resistant and highly effective antifouling ceramic tile and the preparation method thereof according to claim 1, characterized in that: In the step S1, during the mixing process, it is necessary to ensure that all raw materials are evenly distributed to avoid agglomeration and segregation; the mixing time is controlled to be 30-60 minutes, and the specific time depends on the type and efficiency of the mixer; after the mixing is completed, the mixture should be sampled and tested to ensure that the mixing ratio is accurate; In step S2, the grinding and refining is carried out in a ball mill or a vibration mill. The purpose of the grinding and refining is to ensure that the particle size distribution of the raw material is uniform and the average particle size is controlled within the range of 1-10 microns. The grinding and refining time is 2-4 hours, and the specific time depends on the initial particle size of the raw material and the required particle size distribution.
6. The super wear-resistant and highly effective antifouling ceramic tile and the preparation method thereof according to claim 1, characterized in that: In step S3, the purpose of pulverizing and refining is to ensure that the particle size distribution of the raw material is uniform, and the average particle size is controlled within the range of 1-10 microns; the pulverizing and refining time is 2-4 hours, and the specific time depends on the initial particle size of the raw material and the required particle size distribution; In step S4, the crushed raw materials are added with 20% to 30% of water of the total raw material mass, and stirred evenly in a mixer to prepare a ceramic slurry; the consistency of the slurry is controlled within an appropriate range to facilitate subsequent pressing and molding; the pH value of the slurry needs to be adjusted to 7-8 to ensure optimal stability and fluidity.
7. The super wear-resistant and highly effective antifouling ceramic tile and the preparation method thereof according to claim 1, characterized in that: In step S5, during the pressing process, the pressure is controlled at 30-50 MPa to obtain a dense and uniform tile body; the pressing time is 15-30 seconds, and the specific time depends on the performance of the press and the characteristics of the slurry; the thickness and size of the body after pressing must meet the predetermined specifications.
8. The super wear-resistant and highly effective antifouling ceramic tile and the preparation method thereof according to claim 1, characterized in that: In step S6, the drying process is carried out in a drying chamber or a tunnel dryer, the temperature is controlled at 60-100°C, and the drying time is 12-24 hours, and the specific time depends on the thickness of the green body and the performance of the drying equipment; In step S7, the sintering temperature is controlled at 1200-1300°C, the heating rate is 2-5°C / minute, and the insulation time is 1-2 hours to ensure that the internal structure of the tile is uniform and dense; during the sintering process, the atmosphere in the furnace must be strictly controlled to avoid the influence of oxidation or reduction atmosphere on the performance of the tile.
9. The super wear-resistant and highly effective antifouling ceramic tile and the preparation method thereof according to claim 1, characterized in that: In the step S8, after sintering is completed, the ceramic tile is allowed to cool naturally to room temperature; the natural cooling rate should not be too fast to prevent the ceramic tile from cracking due to a large temperature gradient; the cooling time is 12-24 hours, and the specific time depends on the size and thickness of the ceramic tile; In step S9, during the polishing process, a polishing machine is used in conjunction with polishing abrasive blocks, and the abrasive blocks are used in sequence from coarse to fine particles to gradually improve the glossiness of the tile surface; the polishing pressure and speed need to be adjusted according to the hardness of the tile and the required polishing effect.
10. The super wear-resistant and highly effective antifouling ceramic tile and the preparation method thereof according to claim 1, characterized in that: In step S10, the coating material may be nano-ceramic or silicate, and the coating may be applied by spraying, brushing or dipping; the coating thickness is controlled to be 5-20 microns to ensure sufficient wear resistance and anti-fouling performance; after applying the coating, it is necessary to ensure that the coating evenly covers the surface of the tile; In the step S11, the curing process is carried out in an oven, the temperature is controlled at 100-150° C., and the curing time is 30-60 minutes.